Assessment of Individual Susceptibility to Baseline DNA and Cytogenetic Damage in a Healthy Turkish Population: Evaluation with Lifestyle Factors - (:unkn) unknown (MARY ANN LIEBERT INC, 2012)
Background: Cytogenetic biomarkers are most frequently used well-established endpoints in human population studies with their sensitivity for measuring exposure to genotoxic agents. They have an important role as early predictors of cancer risk. Identification of individual genotypes of metabolic gene polymorphisms helps to understand the modulation of cancer susceptibility by environmental exposures, such as cigarette smoking and other lifestyle factors. Aim: To evaluate individual susceptibility to chemicals, we determined individual DNA damage related to glutathione S-transferase (GST) genotypes (GSTM1, GSTT1, and GSTP1) in a Turkish population. Methods: Peripheral blood lymphocytes (PBL) and DNA samples of 127 subjects were analyzed for the presence of DNA damage, using single-cell gel electrophoresis (the Comet assay), and for cytogenetic parameters (chromosomal aberrations [CAs], bleomycin-induced CA, and a cytokinesis-blocked micronucleus assay), and the polymerase chain reaction/restriction fragment length polymorphism method, respectively. Results: Individuals carrying a GSTT1-null allele showed higher frequencies of CA and micronucleus (MN) (p = 0.026, p = 0.003, respectively), whereas the GSTM1-null and GSTP1 mutant genotypes did not show any differences in cytogenetic parameters. Our findings demonstrated that none of the lifestyle factors (smoking, alcohol drinking, dietary habits, vitamin intake, and physical activity), except for vitamin intake (p = 0.002), were significantly associated with the studied cytogenetic parameters. Conclusion: Our results suggest that the GSTT1 gene polymorphism may influence the baseline cytogenetic frequency in a healthy population.
Keywords: PERIPHERAL-BLOOD LYMPHOCYTES; XENOBIOTIC-METABOLIZING ENZYMES; SISTER-CHROMATID EXCHANGE; BLOCK MICRONUCLEUS ASSAY; S-TRANSFERASE P1; CHROMOSOMAL-ABERRATIONS; COMET ASSAY; GENETIC POLYMORPHISMS; T1 POLYMORPHISMS; SCORING CRITERIA